Treating refractory wounds with necrotic tissue, using wound gel and dietary modifications - Shannon Payseur; Warren Lesser; Kenneth Gossett; Shashi, Manish (Asian Journal of Medical Sciences, 2023)
Background: A certified hyperbaric and wound care specialist in the South-west US evaluated three patients who presented with refractory wounds containing substantial necrotic tissue. Aims and Objectives: The primary aim/objective of this study was for the investigator to ascertain if the wound gel, in combination with dietary changes and standard hyperbaric oxygen treatment (HBOT) when placed on refractory wounds evidentiary with necrotic tissue, would result in favorable wound healing outcomes. This study’s secondary aim/objective was to determine if this treatment approach could result in avoiding costly and deleterious, life-changing amputations, and/or surgical reconstructions. Materials and Methods: The physician investigator conducted this qualitative method case study during her regular professional medical practice. She selected study subjects based on the exigency of patients’ needs. The three subjects selected met three inclusion criteria. The first inclusion criterion was that the patient had at least one serious refractory wound, which wound did not respond to any previous treatment regimens at any treatment center. The second inclusion criterion was that significant necrotic tissue was evidentiary in the wound(s). The third inclusion criterion was that each patient was facing traumatic surgical intervention – either amputation or excision with reconstruction. The investigator measured wound diameters and tracked the time to wound closure and wound healing. In addition, the investigator noted patient comments during the wound healing. Results: In two cases, patients were scheduled for umbilical reconstruction; in the third, the patient was scheduled for a frontal foot amputation. In 10 weeks, the three patients experienced complete wound healing or substantial wound resolution. Case #2 patient initially only received HBOT at a different wound center and was emergently admitted to the hospital after 2 weeks of HBOT (no dietary alteration or specialized wound gel application). The patient underwent wide excisional debridement with general surgery but received the trifurcated treatment regimen after discharge, resulting in wound healing within 10 weeks. Conclusion: These results warrant further study with more subjects to determine the replicability of findings. If the results are generalizable to this population of patients suffering from advanced refractory wounds and facing limb amputations, the health and quality-of-life benefits for these patients and the prospective cost savings on the U.S. health system could be incalculable.